The impact of the use of printed instructional materials with native language support on immigrant students’ performance in high school mathematics - Ramm, Luba L. (Kansas State University, 2006)
This study explored the benefits of one instructional strategy on the development of English skills and on the achievement in academic school areas by linguistically different high school students. The specific strategy chosen was the use of printed instructional materials with native language support in subject matter areas. The academic performance of adolescent immigrant students having printed instructional materials with native language support in one subject area was compared to their academic performance in the same subject without using native language support. In addition, the study explored qualitatively the perceptions of the use of printed instructional materials with native language support in subject matter areas among learners, their parents, and ESL as well as subject area teachers. The statistical analysis of linguistically different high school students’ test performance in geometry showed that instructional materials with native language support contributed significantly to the improvement of students’ performance. The comparison of ESL students’ performance with the performance of non-ESL students demonstrated that, on average, ESL students who were lagging behind the non-ESL students before the treatment was applied, outperformed the non-ESL students when native language support was available and then closed the gap between ESL and non-ESL students on subsequent material without native language support. The student survey demonstrated the ESL students’ preference for having regular subject area textbooks in English containing page by page glossaries and explanations in their native language. Parents’ responses to questionnaires showed that the instructional materials with native language support enabled parents to understand what their children study in school and to help their children with their school work. Both ESL and the majority of geometry teachers noticed the positive changes in their ESL students when ESL students were provided with materials containing native language support. All parties participating in the research supported the idea of providing adolescent immigrant students with printed instructional materials containing native language support in all academic subject areas, which would require a collective effort of educators in the fields of science, mathematics, social studies, language arts as well as special education teachers.
Keywords: ESL, adolescents; Cognitive approach; Education, Bilingual and Multicultural (0282)